Non-Saccharomyces yeasts as bioprotection in the composition of red wine and in the reduction of sulfur dioxide. (September 2021) - Windholtz, Sara; Redon, Pascaline; Lacampagne, Soizic; Farris, Laura; Lytra, Georgia; Cameleyre, Margaux; Barbe, Jean-Christophe; Coulon, Joana; Thibon, Cécile; Masneuf-Pomarède, Isabelle
Abstract: Non- Saccharomyces yeasts have been used for many years due to their technological potential, particularly as a "booster" of wine fruity aroma in mixed fermentations with Saccharomyces cerevisiae . Recently, a new application has emerged, bioprotection, which consists in colonizing the environment in the context of sulfite reduction in wines. The chemical and sensory impact of non- Saccharomyces yeast according to different modes of application in a context of fermentation without addition of SO2 was evaluated through trial with Merlot N. ( Vitis vinifera L.). An effective niche occupation by non- Saccharomyces yeasts was highlighted during the prefermentary stages by Quantitative-PCR and MALDI-TOF MS identification. Chemical analysis (GC-MS and GC MS/MS) of finish wine showed the significant impact of the dose applications, with bioprotection characterized by linear esters and sequential application by acetates of higher alcohol contents. Moreover, a separation according to the species used in bioprotection was revealed. Finally, using a panel trained, the sensory analysis confirmed that the use of non- Saccharomyces yeast was a fruity booster in sequential inoculation and, to a less extent, when used as bioprotection. This study shows for the first time that the use of non- Saccharomyces yeast as a bioprotection has a significant impact on the aromatic profile of wines. Highlights: Occupying the niche by T. delbrueckii as a bioprotection, unlike S. cerevisiae . The dosage of non- Saccharomyces significantly impact the chemical composition of red wine. Impact of bioprotection on the chemical and aromatic profile red wine in low SO2 .